Research progress on the mechanisms of CSF3R mutations in leukemogenesis and treatment strategies - Ningxuan Wang; Xiangan Li; Chenyang She; Jun Zhang (Cancer Cell International)
Abstract Leukemia is a malignant clonal disease originating from hematopoietic stem cells. Its pathogenesis is associated with multiple factors, including biological, physical, chemical, genetic, and other hematological diseases. Previous studies have shown that a high mutation rate (>80%) of colony-stimulating factor receptor 3 (CSF3R) is observed in chronic neutrophilic leukemia (CNL) patients, and these mutations activate downstream signaling pathways, leading to the proliferation of neutrophils. In-depth research on the CSF3R genes and their related mechanisms will help further reveal the mechanisms of leukemia development and provide potential targets for treatment. Therefore, this paper mainly focuses on the roles of colony-stimulating factor 3 (CSF3R) in hematopoiesis and the occurrence of leukemia, with particular attention to the roles of CSF3R in the JAK-STAT, PI3K-AKT, and MAPK-ERK signaling pathways. Graphical abstract